Knowledge, attitudes and practices of students in matric regarding smoking - Mokonoto, Maggie Dimakatso (My University, 2003)
Smoking is a preventable cause of death. Young people start smoking at an early age due to certain external influences such as peer pressure, advertising etc. Once they start smoking, they often remain smokers forever because of the addictive effects of nicotine. The international studies show that the high morbidity and mortality rates caused by cigarette smoking can be reduced if health promotion strategies target school going children. The aim of the study was to investigate knowledge, attitudes and practices of students in matric as regards smoking in the Greater Tshwane Metropolitan area (Pretoria). This will inform the health promotion programmes, in particular health education, dealing with tobacco smoking prevention and control in schools
A thesis submitted in fulfilment of the requirements for the degree of Master of Public Health in the department of school of Public Health Faculty of Health Sciences University of the Witwatersrand Johannesburg, 2003
Keywords: Smoking; Adolescent Behavior; Health Knowledge, Attitudes, Practice